Associations Between 30-Day Mortality, Specialist Nursing, and Daily Physician Ward Rounds in a National Stroke Registry. Issue 9 (September 2018) - Paley, Lizz; Williamson, Elizabeth; Bray, Benjamin D.; Hoffman, Alex; James, Martin A.; Rudd, Anthony G.
Abstract : Background and Purpose—: Well-organized stroke care is associated with better patient outcomes, but the most important organizational factors are unknown. Methods—: Data were extracted from the Sentinel Stroke National Audit Programme of adults with acute stroke treated in stroke hospitals in England and Wales between April 2013 and March 2015. Multilevel models with random intercepts for hospitals were used to estimate the association of each variable with 30-day mortality to estimate the impact of admission to differently organized hospitals. Results—: Of the 143 578 patients with acute stroke admitted to 154 hospitals, 14.4% died within 30 days of admission. In adjusted analyses, admission to hospitals with higher ratios of nurses trained in swallow screening was associated with reduced odds of death ( P =0.004), and admission to hospitals with daily physician ward rounds was associated with 10% lower odds of mortality compared with less-frequent ward rounds (95% CI, 0.82–0.98; P =0.013). Number of stroke admissions and overall ratio of registered nurses on duty at weekends were not found to be independently associated with mortality after adjustment for other factors. Conclusions—: If these associations are causal, an extra 1332 deaths annually in England and Wales could be saved by hospitals providing care associated with a ratio of nurses trained in swallow screening of at least 3 per 10 beds and daily stroke physician ward rounds. Abstract : Supplemental Digital Content is available in the text.